A mixed-methods research approach to the review of competency standards for orthotist/prosthetists in Australia. Issue 2 (June 2015) - Ash, Susan; O'Connor, Jackie; Anderson, Sarah; Ridgewell, Emily; Clarke, Leigh
ABSTRACT: Aim: The requirement for an allied health workforce is expanding as the global burden of disease increases internationally. To safely meet the demand for an expanded workforce of orthotist/prosthetists in Australia, competency based standards, which are up-to-date and evidence-based, are required. The aims of this study were to determine the minimum level for entry into the orthotic/prosthetic profession; to develop entry level competency standards for the profession; and to validate the developed entry-level competency standards within the profession nationally, using an evidence-based approach. Methods: A mixed-methods research design was applied, using a three-step sequential exploratory design, where step 1 involved collecting and analyzing qualitative data from two focus groups; step 2 involved exploratory instrument development and testing, developing the draft competency standards; and step 3 involved quantitative data collection and analysis – a Delphi survey. In stage 1 (steps 1 and 2), the two focus groups – an expert and a recent graduate group of Australian orthotist/prosthetists – were led by an experienced facilitator, to identify gaps in the current competency standards and then to outline a key purpose, and work roles and tasks for the profession. The resulting domains and activities of the first draft of the competency standards were synthesized using thematic analysis. In stage 2 (step 3), the draft-competency standards were circulated to a purposive sample of the membership of the Australian Orthotic Prosthetic Association, using three rounds of Delphi survey. A project reference group of orthotist/prosthetists reviewed the results of both stages. Results: In stage 1, the expert ( n  = 10) and the new graduate ( n  = 8) groups separately identified work roles and tasks, which formed the initial draft of the competency standards. Further drafts were refined and performance criteria added by the project reference group, resulting in the final draft-competency standards. In stage 2, the final draft-competency standards were circulated to 56 members ( n  = 44 final round) of the Association, who agreed on the key purpose, 6 domains, 18 activities, and 68 performance criteria of the final competency standards. Conclusion: This study outlines a rigorous and evidence-based mixed-methods approach for developing and endorsing professional competency standards, which is representative of the views of the profession of orthotist/prosthetists.